The effect of serum levels of vitamin C on asthmatic children: a systematic review - Farhad Heydarian; Hamid Ahanchian; Maryam Khalesi; Saeed Ebrahimi (Reviews in Clinical Medicine, 2016)
Introduction: Asthma is a chronic inflammatory airway disorder that is distinguished by coughing, wheezing, and dyspnea. It is the most common chronic disease among children. Epidemiological trials have suggested that there may be a correlation between vitamin C intake and the incidence of asthma. Specifically, according to these studies, a rapid increase in the occurrence of asthma may be caused by a decreased intake of dietary antioxidants and various vitamins such as vitamin C. A systematic review was performed to determine the role that vitamin C, in terms of both dietary intake and serum levels, had on asthma in children. Methods: PubMed and Scopus databases were searched for studies that provide information on the effects of vitamin C on asthma in children aged between 1 and 17 years. The inclusion criteria specified that the studies involved needed to be cohort and case series involving at least ten patients. Exclusion criteria were non-English articles, case reports, and articles involving children who were aged below or above the age 1 and 17 respectively.Result: A total of 13 studies involving 6503 patients met the inclusion criteria. Dietary vitamin C intake was lower in people with asthma than in those without asthma. Lower quantity dietary intakes and serum levels of vitamin C were also associated with increased incidents of asthma.Conclusion: According to the extracted data, a relatively low dietary intake of vitamin C is associated with an increased risk of asthma and wheezing. Moreover, asthmatic patients who consumed vitamin C exhibited an improvement in their diseases.